Temporal changes in peripheral regional oxygen saturation associated with return of spontaneous circulation after out-of-hospital cardiac arrest: A prospective observational cohort study in Japan. (May 2022) - Taniguchi, Hayato; Abe, Takeru; Doi, Tomoki; Nakamura, Kyota; Matsumoto, Jun; Takeuchi, Ichiro
Abstract: Aim: Temporal changes in cerebral regional oxygen saturation (crSO2 ) are useful for predicting return of spontaneous circulation (ROSC) in out-of-hospital cardiac arrest (OHCA) patients. However, little is known regarding the usefulness of peripheral regional oxygen saturation (prSO2 ) associated with OHCA patient outcomes. This study evaluated the association between temporal changes in prSO2 and ROSC in patients with OHCA. Methods: This was a prospective study at two tertiary emergency centres in Japan. We evaluated the relationship between ROSC and temporal changes in crSO2 and prSO2 . The rSO2 sensor was attached to the patient's forehead and upper arm, and rSO2 was continuously measured until resuscitative efforts were terminated or until the patient with sustained ROSC (>20 min) arrived at the emergency department. Results: We included 145 patients with OHCA, of whom 35 achieved ROSC. Witness status (odds ratio [95% confidence interval]: 11.6 [3.13–58.1]) and ΔprSO2 (1.13 [1.06–1.24]) were significantly associated with ROSC in multiple logistic analysis. In the ROSC group, ΔprSO2 increased earlier than ΔcrSO2 during cardiopulmonary resuscitation. In the non-ROSC group, there was no significant difference between ΔcrSO2 and ΔprSO2, and neither increased before termination of resuscitation (TOR). Conclusion: We demonstrated for the first time that prSO2 is associated with ROSC in OHCA patients and showed that temporal changes in prSO2 could predict ROSC earlier than those in crSO2 . Our findings could provide time to prepare early interventions after ROSC and assist in determining the TOR for OHCA patients in Japan. Further studies are needed to validate these findings.